Persistent Calyxes in Postbloom Fruit Drop: A Microscopy and Microanalysis Perspective - João Paulo Rodrigues Marques; Marcel Bellato Spósito; Lilian Amorim; Gabriel Sgarbiero Montanha; Geraldo José Silva Junior; Hudson Wallace Pereira de Carvalho; Beatriz Appezzato-da-Glória (Pathogens, 2020)
Citrus postbloom fruit drop, caused by Colletotrichum spp., is an important disease in the Americas. The pathogen infects citrus flowers, produces orange-brown lesions on petals, and may cause the abscission of young fruit. In diseased flowers, the calyxes remain attached to the peduncle after the young fruit drop. No anatomical and microanalysis studies have been conducted to determine whether calyx tissues can be infected by Colletotrichum spp. and why calyxes remain attached to the peduncle. Based on light microscopy, we demonstrate that the ovary abscission zone exhibits a separation region composed of layers of thickened lignified walled cells, indicating that abscission involves the disruption of cell walls. The first layers of the protective zone (PZ) are composed of densely packed cells with suberized walls produced by the wound meristem. Beneath the PZ, there is a compact mass of small cells that accumulate starch grains. X-ray fluorescence microanalysis (µ-XRF) confirmed the increased accumulation of calcium in the receptacle of the persistent calyxes compared to non-inoculated citrus flowers. Moreover, the peduncle pith and the receptacle exhibit hypertrophied cells with thick walls that may be related to calyx retention. Fungal structures are not observed inside the persistent calyx tissues.